Metabolic Regulation of Regulatory T Cell Development and Function - Coe, David John; Kishore, Madhav; Marelli-Berg, Federica (Frontiers in Immunology, 2014)
It is now well established that the effector T cell (Teff) response is regulated by a series of metabolic switches. Quiescent T cells predominantly require ATP-generating processes, whereas proliferating Teff require high metabolic flux through growth-promoting pathways, such as glycolysis. Pathways that control metabolism and immune cell function are intimately linked, and changes in cell metabolism at both the cell and system levels have been shown to enhance or suppress specific T cell effector functions. Furthermore, functionally distinct T cell subsets have been shown to require distinct energetic and biosynthetic pathways to support their specific functional needs. In particular, naturally occurring regulatory T cells (Treg) are characterized by a unique metabolic signature distinct to that of conventional Teff cells. We here briefly review the signaling pathways that control Treg metabolism and how this metabolic phenotype integrates their differentiation and function. Ultimately, these metabolic features may provide new opportunities for the therapeutic modulation of unwanted immune responses.